In-vitro Antibacterial and Antifungal Activity of Curcuma Amada Roxb. against Human Pathogens - Kashyap, Nand Kumar; Deepak, Jeetendra; Bhardwaj, Arvind Kumar; Hait, Milan; Pal, Dilipkumar (Trends in Sciences, 2022)
This investigation was conducted to evaluate the antimicrobial effectiveness of the agar disc diffusion method and to determine the inhibition zone of Curcuma amada (CA) rhizome extracts (petroleum ether, dichloromethane, and chloroform) against 12 bacterial species and 4 fungal species. The inhibition zones of the extracts were compared to those of Ciprofloxacin and Griseofulvin for antibacterial and antifungal activities, respectively. The findings revealed that the organisms under examination showed significant inhibition of bacterial as well as fungal development during the experiment and that the typical form of C. amada rhizome can be used to treat bacterial and fungal illnesses. So, this plant could be used to find natural compounds that are bioactive and could be used to make new medicines. HIGHLIGHTS Extracts of amada rhizome were found to protect humans from pathogens aureus bacteria had the highest inhibition zone (17 mm) in dichloromethane extract, whereas B. subtilis and B. pumilus bacteria had the lowest inhibition zone (7.5 mm) in C. amada rhizome petroleum ether extract notatum in petrolieum ether extract and A. niger in chloroform extract had the highest inhibition zones (13.5 mm), whereas P. funiculosum in chloroform extract of C. amada rhizome had the lowest inhibition zone (10 mm) GRAPHICAL ABSTRACT